Relationship between Smoking and Oral Health Problems among People in U-Thong District, Suphanburi Province - Phoophania, Marut; Eungsuwanpanit, Kamoltip (Ratchaphruek Journal, 2020)
This research was a cross sectional study aimed to study demographic data, smoking behavior and oral health problems of smokers in U-thong District, Suphanburi Province, Thailand. The total of 390 samples. Two groups were recruited: 195 persons each in smoking group and non-smoking group. The data were collected by questionnaires and oral examination. The data were analyzed by descriptive statistics and logistic regression. The research results showed that45.13% were the <10 years smokers and the average age was 12 years old. There was a frequency of smoking more than 5 days per week for 69.23%, the quantity of smoking was 10-19 cigarettes per day was 43.08%and the average quantity was 10.20 cigarettes per day. The dental caries was 77.69% and the DMFT was 6.16 teeth per person. The periodontal disease was 69.11%. The relative risk for dental caries of smoking group 2.88 times than non-smoking group and the relative risk for periodontal disease of smoking group 3.89 times than non-smoking group. According to the quantity of smoking per day, the frequency per week and the period of smoking time were all risky factors to cause all oral health problems. Therefore, people with oral health problems to either reduced or stopped smoking to reduce the severity of oral health problems.